2010
DOI: 10.3109/10520290903149620
|View full text |Cite
|
Sign up to set email alerts
|

Binding of cationic dyes to DNA: distinguishing intercalation and groove binding mechanisms using simple experimental and numerical models

Abstract: Simple methods for predicting intercalation or groove binding of dyes and analogous compounds with double stranded DNA are described. The methods are based on a quantitative assessment of the aspect (width to length) ratio of the dyes. The procedures were validated using a set of 38 cationic dyes of varied chemical structures binding to well oriented DNA fibers and assessing binding orientation by linear dichroism and polarized fluorescence. We demonstrated that low aspect ratio dyes bound by intercalation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Localises in nuclear chromatin owing to dsDNA minor groove binding [40,41,70] log P > 8 A I > 8 or if 5 > AI > 3.5 and HGS > 400 (or HGH < À4) or if CBN > 40 and log P > À10…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Localises in nuclear chromatin owing to dsDNA minor groove binding [40,41,70] log P > 8 A I > 8 or if 5 > AI > 3.5 and HGS > 400 (or HGH < À4) or if CBN > 40 and log P > À10…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A cut‐off between intercalation and groove binding is seen at L values corresponding to the length of a base pair. Thus, in the absence of bulky substituents, the boundary between these two mechanisms is 10 simplistic bond number units . Chromatin accumulation also occurs with membrane permeant anionic dyes whose conjugated systems exceed a minimum size, owing to histone binding (8 > log P > 0, Z < 0, CBN > 16).…”
Section: Where Do Dyes Go Inside Live Cells? Predicting Localisationmentioning
confidence: 99%
“…In terms of binding mode, some of the previous reports revealed that AuO binds strongly to the minor groove formed by the AT region of the DNA . On the other hand, few reports have observed that AuO can bind exclusively by the intercalation binding mode or by a mixture of intercalation and groove binding modes. , Generally, the surface of minor grooves with AT-rich sequences has the highest negative electrostatic potentials . Naturally, the cationic AuO prefers to bind to the AT-rich minor grooves of DNA than the minor groove formed by the GC-bps.…”
Section: Resultsmentioning
confidence: 99%
“…The titration data from Figure 3c show that there is no change in shape or peak position for the negative and positive CD bands of MGC with increased dye loading, suggesting that this dye does not change its binding mode from low to high site occupancy. 41 While MGC was suggested to bind both as an intercalator and as a groove binder, 42 the CD data from Figure 3c suggests that intercalation is more likely the binding mechanism. For polyAT the bisignate chiral signal at 600−700 nm is much stronger (Figure S2, SI), that is, the excitonic coupling between intercalated MGC dyes is much stronger compared to dyes intercalated with rdsDNA.…”
Section: ■ Intercalated Dna/mgc Complexmentioning
confidence: 97%